Marriage of Transgender Men and Women from the Perspective of Fiqh Munakahat - Alfi Nur Hidayati; Dita Natasha Irviana; Isnaini Wardatun Nafi’ah (NALAR FIQH: Jurnal Hukum Islam, 2023)
Marriage in Islam is an agreement that binds two people, namely a man and a woman, both parties have fulfilled the prerequisites according to applicable regulations based on willingness and preference to live together in a family, to receive peace and happiness both physically and spiritually. Islam has regulated legal and lawful biological relationships through marriage, but deviations can still occur, whether in the form of adultery, homosexuals, lesbians, bisexuals, and transgenders. In the midst of an increasingly diverse society, the question will inevitably arise about transgender marriage laws in Islam. This the paper uses a qualitative descriptive approach with the library research method. With this research, it aims to find out the marriage law of transgender surgery actors from the perspective of Islamic law. The results of the study show that someone who performs transgender surgery is included in actions that are prohibited or unlawful according to Islam. Meanwhile, when a person performs transgender surgery because they have abnormalities in their genitals, it is permissible to carry out the operation. So when a transgender operation actor wants to carry out a marriage, he uses his status before becoming transgender. For example, his initial status is male, he must marry a woman if he wants his marriage to be valid in the eyes of law and religion.